PENINGKATAN KETERAMPILAN MENULIS DENGAN PENDEKATAN KOMUNIKATIF PRAGMATIK PADA MUATAN PEMBELAJARAN BAHASA INDONESIA DI KELAS IV SDN 04 TAPI SELO - Gusnaini, Gusnaini (STKIP Pesisir Selatan, 2019)
Lack of writing skills to express ideas in class IV SDN 04 Tapi Selo is a problem that must be resolved, because it will have a negative impact on other learning outcomes in school. The problem in writing skills is certainly directly related to skills, listening, reading and speaking. To solve this problem, the authors made improvements by carrying out the Pragmatic Communicative approach to Indonesian language learning, which is a language approach with the context of the meaning of expressions that must be understood by others and in accordance with the situation and conditions of language. The study was conducted in three cycles, from August 24, 2018 to September 22, 2018. The results of the study have shown that the pragmatic communicative approach to learning Indonesian has improved the skills of students, to write their ideas in writing reaching 50%.